Awareness about healthy eating in public school children: An experience report - Moliterno, Amanda; Salvador, Juliene Amanda (Seven Editora, 2023)
It is widely recognized that diet plays a fundamental role in child development, since a healthy diet provides energy and essential nutrients to the body. In addition, the adoption of proper eating habits is associated with better academic and cognitive performance. Therefore, food and nutrition education is an important and necessary topic for children, being especially emphasized in the school environment. DOI:https://doi.org/10.56238/alookdevelopv1-112